Deaf culture exploring deaf communities in the United States - Leigh, Irene 1944-; Andrews, Jean F. 1951-; Harris, Raychelle L. (Plural Publishing, 2018)
"A contemporary and vibrant Deaf culture is found within Deaf communities, including Deaf Persons of Color and those who are DeafDisabled and DeafBlind. Taking a more people-centered view, the second edition of Deaf Culture: Exploring Deaf Communities in the United States critically examines how Deaf culture fits into education, psychology, cultural studies, technology, and the arts. With the acknowledgment of signed languages all over the world as bona fide languages, the perception of Deaf people has evolved into the recognition and acceptance of a vibrant Deaf culture centered around the use of signed languages and the communities of Deaf peoples. Written by Deaf and hearing authors with extensive teaching experience and immersion in Deaf cultures and signed languages, Deaf Culture fills a niche as an introductory textbook that is more inclusive, accessible, and straightforward for those beginning their studies of the Deaf-World"
Keywords: Deaf / United States; Deaf culture / United States; Deaf; Deaf culture; United States